English language education in Jordan: Some recent trends and challenges - Alhabahba, Mohammad Madallh; Pandian, Ambigapathy; Ali Mahfoodh, Omer Hassan (Cogent OA, 2016)
The purpose of this paper is to map out the status of English language teaching (ELT) as practised in the Arab World and, specifically, in Jordan today. The study also aims to bring into focus significant issues that need to be addressed in ELT in the Arab World. This paper presents a review of the current status of English language education, with an emphasis on the need for urgent reforms in the teaching of English in the Arab World. Further, longitudinal data in respect to classroom and workplace English proficiency are presented. English language education seems to be up-to-date teacher-centred and bound to other issues such as teaching the textbook rather than focusing on developing lifelong strategies. There is a critical need for writing national standards for English language professional development programmes that should be based on the findings of sound research. The paper highlights the significance of teaching English language through observing and reviewing the current practices.